Determinants Of Credit Sources Utilized By Small Scale Arable Crop Farmers In Imo State, Nigeria - G. N, Ben-Chendo; I., Oshaji; G. O, Iweanya (Advances in Social Sciences Research Journal, 2018)
Credit is not only one of the critical inputs in agriculture but is also an effective means of rural development. The study determined the sources utilized by small-scale arable crop farmers in Imo state, Nigeria. 80 respondents were randomly selected from 16 villages in one local government area selected at random among the 27 local government areas in Imo state, Nigeria and interviewed using structured questionnaire. The data were collected and analysed using descriptive statistics such as mean, percentages and frequency distributions and Multinomial logit regression model. The study revealed that majority (41.25%) of the farmers in the study area were middle-aged farmers between the ages of 30-49years and equal number of male and female arable crop farmers in the study area were interviewed of which majority (78.75%) were married and also had basic education (82.5%). The major source of credit utilized by the respondents in the study area is esusu (30%) followed by village cooperatives (17.5%) and then family and friends (12.5%). Results showed that very few farmers in the area used credit from banks (2.5%). Furthermore, the likelihood ratio statistics as indicated by 2 (80.84) are highly significant and had strong explanatory power to predict farmers choices. Household size, interest rate, farm size, value of assets and age were the major significant determinants of credit sources. It is recommended that credit should be extended more to respondents with higher age and low family size and credit institutions should reduce the long process involved in obtaining loan from their institutions.